A feasibility study of psychological first aid as a supportive intervention among police officers exposed to traumatic events - Geoffrion, Steve; Leduc, Marie-Pierre; Bourgouin, Elody; Bellemare, François; Arenzon, Valérie; Genest, Christine (Frontiers in Psychology, 2023)
Introduction – Police officers are often exposed to traumatic events, which can induce psychological distress and increase the risk of developing post-traumatic stress injuries. To date, little is known about support and prevention of traumatic events in police organizations. Psychological first aid (PFA) has been promoted as a promising solution to prevent psychological distress following exposure to a traumatic event. However, PFA has not yet been adapted to policing reality, let alone to the frequent exposure to traumatic events faced by this population. This study aimed to evaluate the feasibility of PFA as an early intervention for the prevention of post-traumatic stress injuries among police officers in Quebec, Canada. Specifically, the objectives were to evaluate: (1) the demand; (2) the practicality; and (3) the acceptability of PFA in a police organization. Methods – A feasibility study was conducted to evaluate the implementation of PFA among Quebec’s provincial police force. To do so, 36 police officers participated in semi-structured interviews between October 26th, 2021, and July 23rd, 2022. Participants were comprised of responders (n=26), beneficiaries (n=4) and managers (n=6). Interviews were transcribed, coded, and evaluated according to a thematic analysis. Results – Eleven themes emerged from participants’ responses. Results suggested that PFA met individual and organizational needs. References were also made regarding the impacts of this intervention. Moreover, participants provided feedback for improving the implementation and sustainability of a PFA program. All three groups of participants shared similar thematic content. Discussion – Findings revealed that implementation of a PFA program in a law enforcement agency was feasible and could be accomplished without major issues. Importantly, PFA had beneficial consequences within the organization. Specifically, PFA destigmatized mental health issues and renewed a sense of hope among police personnel. These findings are in line with previous research.